Diabetes mellitus: evaluation and control through laboratory tests in a private service from Teresina, Piauí, Brazil (Research, Society and Development, 2020)
Diabetes mellitus (DM) is a chronic disease that affects millions of people worldwide, directly influencing the quality of life of the individual, is triggered when the action or production of insulin becomes deficient, which generates a series of chronic complications. , and it is a worldwide public health problem, leading to a marked reduction in life expectancy of the affected, with the vast majority dying due to secondary complications of the disease. The aim of the present study was to characterize the prevalence of diabetes mellitus and to evaluate the control of diabetes mellitus through glycated hemoglobin and fasting glucose tests in the study population in a private service of Teresina - Piaui. The data obtained for the research were collected in an electronic secondary database in the Proanalises Diagnostics laboratory, data from which were obtained from medical requests. The study is characterized by being descriptive, with a quantitative approach of the subject, where the statistical analyzes were calculated using a package statistical science (SPSS) -version 20.0 for Windows. A total of 251 patients with diabetes mellitus over 18 years of age of both sexes were evaluated. In this study, glucose and A1C levels were correlated and altered, demonstrating the need for glycemic control. Maintaining glucose levels between 100 and 125 mg / dl and A1C levels between 5 and 7% should be a goal of all diabetic patients, thus preventing secondary complications.